Evaluation of the relationship between homocysteine levels and bone mineral density in postmenopausal women. (4th March 2022) - Garcia-Alfaro, P.; Rodriguez, I.; Pascual, M. A.
Abstract: Objective: The current study aimed to evaluate the relationship between homocysteine (Hcy) levels and bone mineral density (BMD) in postmenopausal women. Methods: The present, cross-sectional study included 760 postmenopausal women. The following variables were recorded: age, age at menopause, body mass index (BMI), BMD (measured by dual-energy X-ray absorptiometry [DXA] scanning and expressed as lumbar, femoral neck and total hip T -scores), smoking status, biochemical parameters (Hcy, creatinine, calcium, phosphorus, vitamin D and parathormone levels) and vitamin D supplementation. Results: The mean age of the sample population was 56.4 ± 5.77 years and the mean age at menopause was 49.9 ± 3.62 years. The mean BMI was 25.2 ± 4.49 kg/m 2 . In the current study, a comparison of the subjects with osteoporosis, osteopenia and normal BMD revealed that the subjects in the low BMD group were significantly older ( p < 0.001), had a lower age at menopause ( p < 0.001) and had lower BMI ( p < 0.001). There was no statistically significant difference among the groups with regard to the plasma levels of Hcy ( p = 0.946). The levels of Hcy were positively correlated to the creatinine levels ( r = 0.21). The present study did not observe any significant correlations between the Hcy levels and other parameters. Conclusions: In the present study, 15.3% of the subjects had hyperhomocysteinemia and 62.11% had low BMD. The current results obtained from a group of postmenopausal women suggest that the plasma levels of Hcy are not related to BMD in the lumbar spine (L1–L4), femoral neck and total hip. In the current study, age, age at menopause and low BMI were observed to be associated with low BMD.